2015
DOI: 10.3892/ol.2015.3544
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of central lymph node metastasis in 392 patients with cervical lymph node-negative papillary thyroid carcinoma in Eastern China

Abstract: Abstract. Central lymph node metastasis (CLNM) is common in papillary thyroid microcarcinoma (PTMC). The aim of the present study was to investigate the risk factors associated with CLNM in clinical lateral cervical lymph node-negative (cN0) PTMC in Eastern China. A total of 392 patients with confirmed PTMC by histological examination who underwent thyroidectomy and central neck lymph node dissection (CND) between May 2011 and October 2012 at the First Affiliated Hospital of Wenzhou Medical University (Wenzhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
2
19
1
Order By: Relevance
“…17 Emerging evidences have demonstrated decreased disease-free survival rate and increased mortality associated with regional LNM. 18 Even though lots of novel methods were emerging to target cancer cells and LNM of PTC, 19 LND is generally recommended in PTC patients with LNM. However, the extensive postoperative complications caused by LND should not be ignored which will reduce the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Emerging evidences have demonstrated decreased disease-free survival rate and increased mortality associated with regional LNM. 18 Even though lots of novel methods were emerging to target cancer cells and LNM of PTC, 19 LND is generally recommended in PTC patients with LNM. However, the extensive postoperative complications caused by LND should not be ignored which will reduce the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of LNM has increased from 41% to 64%. 24 Although preoperative US is widely used, pathologically confirmed lymph nodes are not discovered before surgery. Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to evaluate the benefits of prophylactic ipsilateral CND with total thyroidectomy in cN0 PTC patients. Several studies have reported the risk factors of central and lateral neck LNM [7,14,16,17]. Male sex, age ( > 45 years), tumor size ( > 5 mm), lower lobe, total tumor diameter ( > 10 mm), and extracapsular spread were statistically significant factors for CLNM in multivariate analysis [7].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have reported the risk factors of central and lateral neck LNM [ 7 , 14 , 16 , 17 ]. Male sex, age (>45 years), tumor size (>5 mm), lower lobe, total tumor diameter (>10 mm), and extracapsular spread were statistically significant factors for CLNM in multivariate analysis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation